Addressing Crisis in Myanmar: The Role of NGOs in Promoting International Human Rights Standards - Khairunnisa, Ainna; Aiyub Kadir, M.Yakub; Mahfud, Mahfud (Udayana Journal of Law and Culture; Vol 7 No 1 (2023)DO - 10.24843/UJLC.2023.v07.i01.p05, 2023)
The Rohingya people have been victims of alleged severe human rights violations committed by the Myanmar government. In response to this situation, the United Nations (UN) has adopted some measures, including a United Nations General Assembly Resolution (UNGAR) A/RES/74/246 of 2019 that, inter alia, determines Non-Governmental Organizations (NGOs) as one of the key players in implementing its mandate. In practice, the NGOs' lack of international legal standing resulted in challenges in their operation. This paper examines the legal standing of NGOs' operations under international law. Specifically, it investigates NGOs' contributions to implementing UNGAR 74/246 in dealing with human rights violations in Myanmar. This article is based on legal research that combines library study and field research. The result indicated that Article 71 of the UN Charter needs to clarify the legal standing of NGOs’ operation in the international sphere, mainly to implement international human rights norms. In the context of the crisis in Myanmar, the NGOs have played a role as mandated by the UNGAR, including investigating gross human rights violations, providing gender-based protection and assistance, and assisting Myanmar in providing humanitarian assistance to all internally displaced persons within Rakhine. This paper recommends that all stakeholders cooperate to support the effectiveness of NGOs' contributions and peace-building efforts in Rakhine to achieve justice for all people in Myanmar.